Given:
The function is:
[tex]f(x)=4x^5-8x^4+8x^2-4x[/tex]
To find:
The roots of the given equation.
Solution:
We have,
[tex]f(x)=4x^5-8x^4+8x^2-4x[/tex]
For roots, [tex]f(x)=0[/tex].
[tex]4x^5-8x^4+8x^2-4x=0[/tex]
[tex]4x(x^4-2x^3+2x-1)=0[/tex]
[tex]4x((x^4-1)+(-2x^3+2x))=0[/tex]
[tex]4x((x^2+1)(x^2-1)-2x(x^2-1))=0[/tex]
On further simplification, we get
[tex]4x(x^2+1-2x)(x^2-1)=0[/tex]
[tex]4x(x-1)^2(x+1)(x-1)=0[/tex]
[tex]4x(x+1)(x-1)^3=0[/tex]
Using zero product property, we get
[tex]4x=0[/tex]
[tex]x=0[/tex]
Similarly,
[tex]x+1=0[/tex]
[tex]x=-1[/tex]
And,
[tex](x-1)^3=0[/tex]
[tex]x=1[/tex]
Therefore, the zeroes of the given function are [tex]-1,0,1[/tex] and the factor form of the given function is [tex]f(x)=4x(x+1)(x-1)^3[/tex].